Kolon: Den oversete konnektor - Eskesen, Helle; Fuglsang, Hanne (HERMES - Journal of Language and Communication in Business, 1998)
The object of study in this article is the analysis of what relations can be established by the colon in written French. The article is the outcome of our cand.ling.merc. thesis from June 1997. Our aim was then to examine how these relations can be expressed in written Danish and whether the colon can be preserved or not. In cases where these relations are not usually signalled by the Danish colon, we will examine what operations are necessary in order to render the meaning in idiomatic Danish. In this article we would like to give a brief account of our findings.